PREDIKSI UMUR DAN KEANDALAN RIPPER TIP PADA BULLDOZER CATERPILLAR D10T DENGAN METODE WEIBULL - Arifin, Fadhilah Akmal Rofiq; Prihadianto, Braam Delfian; Sugiyanto, Sugiyanto; Bahiuddin, Irfan (Jurnal Teknologi Terpadu, 2024)
Ripper tip is one of the hard steel-based components on heavy equipment with a function to protect the ripper tip when breaking the density of soil and rock material (ripping). Friction between rock surfaces and ripper tips results in wear on ripper tips that require periodic replacement. Caterpillar D10T bulldozer owned by PT. XYZ underwent replacement ripper tip components that did not match the recommended age. This study aims to improve the accuracy of replacement planning and analyze the reliability level of ripper tip components. This study used the Weibull distribution method in analyzing the data. The data used is data on ordering and replacing ripper tip components from 2019 to 2021. The object of research was carried out on three units of Caterpillar D10T bulldozers used by PT. XYZ in an open pit mining project in Batulicin District, Tanah Bumbu Regency, South Kalimantan Province. This study shows that the average age of components in the three research objects has differences from the average life of ripper tip components on bulldozers A, B, and C is 369.75 hours, 329.63 hours, and 291.39 hours. The reliability of ripper tip components on the three bulldozers showed a decrease with the increase in operating time while the failure rate of the ripper tip components of the three bulldozers showed an increase with the increased operating time.